Videoconferences of Infectious Diseases: An educational tool that transcends borders. A useful tool also for the current COVID-19 pandemic. - Jose Armando Gonzales Zamora; Jorge Alave; Daniela de Lima Corvino; Anmary Fernandez (My University, 2020)
Not available.
Keywords: Pandemic; Coronavirus disease 2019 (COVID-19); Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2); 2019-20 coronavirus outbreak; Virology; Infectious disease (medical specialty); Medicine; Disease; Outbreak; Pathology; Pandemic; Coronavirus disease 2019 (COVID-19); Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2); 2019-20 coronavirus outbreak; Virology; Infectious disease (medical specialty); Medicine; Disease; Outbreak; Pathology; COVID-19; COVID-19; COVID-19; Communicable Diseases; Communicable Diseases; Communicable Diseases; Education, Medical, Continuing methods; Education, Medical, Continuing methods; Education, Medical, Continuing methods; Humans; Humans; Humans; Pneumonia, Viral epidemiology; Pneumonia, Viral epidemiology; Pneumonia, Viral epidemiology; Telemedicine methods; Telemedicine methods; Telemedicine methods; Coronavirus Infections epidemiology; Coronavirus Infections epidemiology; Coronavirus Infections epidemiology; Education, Distance methods; Education, Distance methods; Education, Distance methods; Internationality; Internationality; Internationality; Videoconferencing; Videoconferencing; Videoconferencing; Pandemics; Pandemics; Pandemics; Social Sciences Social Sciences Education Education during COVID-19 pandemic; Social Sciences Psychology Clinical Psychology COVID-19 and Mental Health; Health Sciences Medicine Public Health, Environmental and Occupational Health Telemedicine and Telehealth Implementation